2005
DOI: 10.1038/sj.jhh.1001847
|View full text |Cite
|
Sign up to set email alerts
|

The effect of treatment on health-related quality of life in patients with hypertension and renal artery stenosis

Abstract: The quality of life in patients with hypertension is considered to be impaired mainly by side effects of antihypertensive drug therapy. Since balloon angioplasty for renal artery stenosis has a medication-sparing effect, it may lead to an improvement in quality of life. The objective of the study is to compare the effect of antihypertensive drug therapy and balloon angioplasty on quality of life in patients with hypertension and renal artery stenosis. We compared the quality of life in 56 patients randomised t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
1
6
1
Order By: Relevance
“…241,460 Also, quality of life scales may be relevant to evaluate. 242 Such scales are strictly speaking only ordinal, but can for practical purposes often be treated as continuous outcomes. A specific issue is that quality of life scores have ceiling effects, because minimum and maximum scores apply.…”
Section: 1 Examples Of Linear Regressionmentioning
confidence: 99%
“…241,460 Also, quality of life scales may be relevant to evaluate. 242 Such scales are strictly speaking only ordinal, but can for practical purposes often be treated as continuous outcomes. A specific issue is that quality of life scores have ceiling effects, because minimum and maximum scores apply.…”
Section: 1 Examples Of Linear Regressionmentioning
confidence: 99%
“…5,6 Factors leading to this effect have been considered both disease's complications and medication's side effects. 7,8 In addition, low levels of health-related quality of life (HRQOL) implicate the cardiovascular outcome in this group of patients. 9 Hypertensives tend to demonstrate impaired performance in various dimensions of HRQOL as in general well-being, functional capacity and symptoms of psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent update, this same group reported that the reduction in medications did not result in any discernible increase in health-related quality of life. 154 All of these trials were relatively small and significantly underpowered to detect meaningful differences in "hard" outcomes such as survival, freedom from adverse cardiovascular events, and the development of dialysis-dependent renal failure. Furthermore, the study excluded patients with severe baseline renal function impairment, 26,151 suffered from extensive crossover between treatment groups, 150,151 did not incorporate renin-angiotensin-based antihypertensive agents into medical management, 26 and used angioplasty without stenting for procedural management.…”
Section: Completed Trialsmentioning
confidence: 99%
“…The authors found no significant difference in event-free survival between treatment groups at a median follow-up of 74 months, but did note a trend towards decreased mortality in patients with renal insufficiency treated surgically. These surgical clinical trials also possess significant limitations: outdated endovascular technology was used, 149 medical treatment was incompletely described, 152,154 or statistical power was severely limited to assess meaningful survival and freedom from event outcomes. 149,152,154 These trials 149,152 were assessed as having poor quality data by the AHRQ review and in the compendium of data examined by the MedCAC.…”
Section: Completed Trialsmentioning
confidence: 99%